The Inspiring War Cry of "Agi Idup Agi Ngelaban" - Regina Garai, Abdullah; Neilson Ilan, Mersat (Tun Jugah Foundation, 2024)
A recorded account of field observations, experiences and reflection when carrying out fieldworks on various parts of Sarawak for a book on Iban Trackers and Sarawak Rangers. It is found that the battle cry of Agi Idup Agi Ngelaban (As Long As I Live, I will Fight) really inspired frontliners in the security force, igniting unwavering determination to defend the country tirelessly, even at the cost of their own lives. Such fighting spirit has long been synonymous with the Sarawak Rangers. The history of Sarawak Rangers can be traced back to the formation of a security force called the fortmen during Brooke's era. This article is based on the narratives shared by key informants who served as Iban Trackers, Sarawak rangers and even Border Scouts.